2018
DOI: 10.3389/fmed.2018.00044
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Quadratus Lumborum Block and ERAS

Abstract: The use of truncal nerve blocks has been described since 2001. Since then, there have been many studies trying to understand the ideal clinical scenarios for its use. Since 2001, the transversus abdominis plane block has evolved in many ways including from landmark based technique to ultrasound guided and more recently, into the quadratus lumborum (QL) block. Its anatomical placement, concentration of local anesthetic, volume of local anesthetic, and anatomic placement have all been raised as clinical question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
105
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(125 citation statements)
references
References 68 publications
1
105
2
2
Order By: Relevance
“…Technically, full visualization of the needle tip during the injection is essential due to the closeness of the administration site to the abdominal structures. Since the frequency of using local anesthesia is higher than peripheral nerve block administration, it has been reported that this may cause potential local anesthetic systemic toxicity (LAST) related complications due to systemic absorption [30]. Although it was found that local anesthetic levels after QLB did not reach a toxic dose, we think that further studies are needed to quantify the potential risk [21].…”
Section: Discussionmentioning
confidence: 84%
“…Technically, full visualization of the needle tip during the injection is essential due to the closeness of the administration site to the abdominal structures. Since the frequency of using local anesthesia is higher than peripheral nerve block administration, it has been reported that this may cause potential local anesthetic systemic toxicity (LAST) related complications due to systemic absorption [30]. Although it was found that local anesthetic levels after QLB did not reach a toxic dose, we think that further studies are needed to quantify the potential risk [21].…”
Section: Discussionmentioning
confidence: 84%
“…We felt that the aforementioned analgetic scheme has remarkable efficacy in pain relief, especially for patients who are involved in the enhanced recovery programs. Therefore, this study focused on whether the QLB may enable an increased analgesic effect and the role it plays in the combination of a typical multi-modal analgesia [33,34]. A recent study by Aditianingsih et al…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of action of QLB is not entirely clear and the spread of local anaesthetic is quite varied according to technique. 17 Hence, clinicians should be aware of lower leg muscle weakness and sensory changes during post-anaesthesia care after performing QLB, and patients should be informed of the possibility of both numbness and weakness as potential side-effects as part of their preoperative consent. Some limitations should be considered in this study.…”
Section: Discussionmentioning
confidence: 99%